Laminating Fabrication of Bifacial Organic-Inorganic Perovskite Solar Cells - Yujing Yang; Yue Zhu; Xiaoxiao Wang; Qi Song; Chao Ji; Huimin Zhang; Zhiqun He; Chunjun Liang (International Journal of Photoenergy)
Bifacial solar cells based on organic-inorganic perovskite are fabricated with a laminating process. The structure of the devices is ITO/SnO2/CH3NH3PbI3/NiOx/ITO, in which both electrodes are the transparent ITO layer. Therefore, the device can receive light from both sides. By laminating the two half-devices, ITO/SnO2/CH3NH3PbI3 and CH3NH3PbI3/NiOx/ITO, at high temperature with pressure, the merging of the middle perovskite layers is enhanced. The optimized bifacial PSCs show a Voc of 0.85 V, FF of 0.58, Jsc of 17.53 mA/cm2, and PCE of 8.47%. The photovoltaic performance varies when the light is illuminated from different sides of the bifacial PSCs. With illumination from the SnO2 side, the Voc and Jsc of the PSCs are apparently higher than those from the NiOx side, suggesting more severe electron-hole recombination at the NiOx/perovskite interface than at the SnO2/perovskite interface.